A COGNITIVE STYLISTIC ANALYSIS OF LEWIS CAPALDI'S SONG “SOMEONE YOU LOVED” - Simanjuntak, Windy Octalin; Saragih, Silvia Efani; Manurung, Rifdah Aatikah; Sihotang, Tiarma; Alivia, Cut Putri; Rangkuti, Rahmadsyah (Ma Chung Press, 2023)
Cognitive stylistics is a branch of linguistics that focuses on the study of how language and literature interact with human cognition and mental processes. This study presents a cognitive stylistic analysis of Lewis Capaldi's song